Effect of geometry on the mechanical response of additively manufactured polymer - Zhang, Yongjie (2021)
In recent years, there is an rise in adoption of additive manufactured parts as end use parts. The increase is especially apparent in an aviation industry, where benefits such as shortened supply chain and parts on demand enabled significant cost savings. One of the most established AM methods, Fused Deposition Modelling™ (FDM), is widely adopted in the aviation industry to manufacture the end use parts. However, to ensure that FDM parts are able to meet functional requirements, extensive characterisation are required to be performed to understand the impact of manufacturing process parameters on the part performance. Due to Process-Structure-Property (PSP) linkage, toolpath can have a significant influence on FDM part performance. Existing research has focused extensively on the impact of process parameters on the FDM part performance. However, it is believed that toolpath planning, which is significantly less extensively studied, can have influence on the part performance. To investigate the effect, this research utilises 5 different tensile specimens and 2 different fabrication methods, namely specimens printed to net shape and specimens machined from a printed plate. It is concluded that the net shape specimens are substantially strengthened and stabilised due to presence of toolpath features. Due to the PSP linkage, the features translate into favourable improvement in mechanical performance which strengthened the net shaped specimens by up to 51%. This paper characterises influence of the toolpath on the mechanical properties and discusses how the toolpath features such as travel distance, thermal history and contours, impact FDM parts which can aid in prediction of performance of FDM structures.